2015
DOI: 10.5194/acp-15-8037-2015
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric ozone variability in the tropics from ENSO to MJO and shorter timescales

Abstract: Abstract. Aura OMI and MLS measurements are combined to produce daily maps of tropospheric ozone beginning October 2004. We show that El Niño-Southern Oscillation (ENSO) related inter-annual change in tropospheric ozone in the tropics is small in relation to combined intra-seasonal/Madden-Julian Oscillation (MJO) and shorter timescale variability by a factor of ∼ 3-10 (largest in the Atlantic). Outgoing longwave radiation (OLR), taken as a proxy for convection, suggests that convection is a dominant driver of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…It is notable that we do not find any sites that show significance of a 7-day cycle (Altshuler et al, 1995;Marr and Harley, 2002;Beirle et al, 2003). Application of this approach to longer time series may also allow the investigation of other characteristic timescales such as North Atlantic Oscillation (NAO) or El Niño-Southern Oscillation (ENSO) (Ziemke et al, 2015).…”
Section: Annual and Daily Cyclesmentioning
confidence: 96%
“…It is notable that we do not find any sites that show significance of a 7-day cycle (Altshuler et al, 1995;Marr and Harley, 2002;Beirle et al, 2003). Application of this approach to longer time series may also allow the investigation of other characteristic timescales such as North Atlantic Oscillation (NAO) or El Niño-Southern Oscillation (ENSO) (Ziemke et al, 2015).…”
Section: Annual and Daily Cyclesmentioning
confidence: 96%
“…DOI: https://doi. org/10.1525/elementa.265.f8 (Sun et al 2014;Ziemke et al, 2015), but this has not been demonstrated for CCMs. A single CCM study, using observed SSTs, reproduced the tropical ozone response to ENSO variability but not shorter timescales related to the MJO (Ziemke et al, 2015).…”
Section: State Of Knowledgementioning
confidence: 99%
“…org/10.1525/elementa.265.f8 (Sun et al 2014;Ziemke et al, 2015), but this has not been demonstrated for CCMs. A single CCM study, using observed SSTs, reproduced the tropical ozone response to ENSO variability but not shorter timescales related to the MJO (Ziemke et al, 2015). Over northern mid-latitudes, ENSO events can affect the interannual variability of hemispheric pollution transport by modulating the strength and position of the subtropical jet stream, particularly in the Pacific-North America sector (Trenberth et al, 1998;Koumoutsaris et al, 2008;Li and Lau, 2012;Lin et al, 2014).…”
Section: State Of Knowledgementioning
confidence: 99%
“…The response is highly linear in the tropics, so La Niña conditions produce an antisymmetric response (DeWeaver and Nigam, 2002). This influence on tropical tropospheric ozone has been observed in satellite data (e.g., Chandra et al, 1998;Thompson et al, 2001;Ziemke et al, 2010Ziemke et al, , 2015 and ground-based measurements (e.g., Fujiwara et al, 1999;Lee et al, 2010). Both chemical transport models (CTMs) driven by analyzed meteorology and free-running models have simulated this impact of ENSO on the tropical ozone (e.g., Sudo and Takahashi, 2001;Zeng and Pyle, 2005;Doherty et al, 2006;Oman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%